2015
DOI: 10.1111/pme.12624
|View full text |Cite|
|
Sign up to set email alerts
|

Treatment of Chronic Lumbosacral Radicular Pain Using Adjuvant Pulsed Radiofrequency: A Randomized Controlled Study

Abstract: The TFEI provided significant short-term pain relief and PRF can be applied in conjunction with TFEI to achieve higher treatment efficacy compared with TFEI alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
85
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(99 citation statements)
references
References 32 publications
4
85
0
10
Order By: Relevance
“…[7,2228] To the best of our knowledge, 5 studies have been published on the effect of monopolar PRF on chronic lumbosacral radicular pain. [23,24,2628] In 2008, Simopoulos et al [27] applied monopolar PRF on 37 patients with chronic lumbosacral radicular pain. Three months after the PRF to the DRG, about half of the patients reported successful pain reduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7,2228] To the best of our knowledge, 5 studies have been published on the effect of monopolar PRF on chronic lumbosacral radicular pain. [23,24,2628] In 2008, Simopoulos et al [27] applied monopolar PRF on 37 patients with chronic lumbosacral radicular pain. Three months after the PRF to the DRG, about half of the patients reported successful pain reduction.…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, Shanthanna et al [26] reported that 6 out of 16 patients with radicular pain in the leg had a good response to PRF. In 2015, Koh et al [24] reported that 31 patients who received combined PRF and TFESI showed higher treatment efficacies for at least 3 months than 31 patients who received TFESI alone in chronic radicular pain. In the same year, Van Boxem et al [28] performed PRF on the DRG of 65 patients with chronic lumbosacral radicular pain, and 50% to 60% showed a positive treatment response; its effect was sustained for at least 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Pulsed radiofrequency is applied with temperature limitation at 42 o Celsius and exposure time of at least 120 seconds 37,38 . b) Spinal cord stimulation In patients with pharmacological treatment limitation and insatisfactory response to percutaneous interventionist treatment, the surgical option is spinal electrode implant to stimulate spinal cord above the conus.…”
Section: Acute Lumbar Radiculopathy With Motor Preservation A) Foramimentioning
confidence: 99%
“…Only a few randomized controlled trials are known that compared PRF as a treatment with other modalities in chronic LRP . In one randomized controlled trial, 70% of patients with LRP receiving PRF reported a significant reduction in pain (≥2 points and/or ≥30% decrease in VAS score) at 2 months, whereas a significant reduction in pain was found in 82% of patients receiving a combination of PRF and CRF at the same time interval.…”
Section: Discussionmentioning
confidence: 99%
“…Also, recent trials have reported beneficial effects of both PRF alone and PRF in combination with CRF for the management of chronic LRP . Recent studies have demonstrated the efficacy of PRF of the DRG alone or in combination with TF epidural steroid injections in the treatment of LRP …”
Section: Introductionmentioning
confidence: 99%